Awareness and understanding of dementia in South Asians: A synthesis of qualitative evidence. (July 2020) - Hossain, Muhammad; Crossland, John; Stores, Rebecca; Dewey, Ann; Hakak, Yohai
Background: Despite a growing elderly South Asian population, little is known about the experience of diagnosis and care for those living with dementia. There have been a number of individual qualitative studies exploring the experiences of South Asian people living with dementia and their carers across different contexts. There has also been a growing interest in synthesizing qualitative research to systematically integrate qualitative evidence from multiple studies to tell us more about a topic at a more abstract level than single studies alone. The aim of this qualitative synthesis was to clearly identify the gaps in the literature and produce new insights regarding the knowledge and understanding of the attitudes, perceptions, and beliefs of the South Asian community about dementia. Methods: Following a systematic search of the literature, included qualitative studies were assessed by two independent reviewers for methodological quality. Data were extracted and pooled using the Joanna Briggs Institute Qualitative Assessment and Review Instrument (QARI). Findings were synthesized using the Joanna Briggs Institute approach to qualitative synthesis by meta-aggregation. Results: Seventeen papers were critically appraised, with 13 meeting the inclusion criteria. Participants were mostly of South Asians of Indian background; followed by Pakistani with a few Sri Lankans. Missing South Asian countries from the current evidence base included those from Bangladesh, Bhutan, Maldives, and Nepal. Three meta-synthesis themes emerged from the analysis: (1) a poor awareness and understanding of dementia, (2) the experience of caregiving, and (3) the attitudes toward dementia care provision. Conclusions: A consistent message from this qualitative synthesis was the limited knowledge and understanding of dementia amongst the South Asians. Whilst symptoms of dementia such as 'memory loss' were believed to be a part of a normal ageing process, some South Asian carers viewed dementia as demons or God's punishments. Most studies reported that many South Asians were explicit in associating stigmas with dementia.